2015
DOI: 10.1038/mi.2014.94
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis caused by vitamin D receptor deficiency confers colonization resistance to Citrobacter rodentium through modulation of innate lymphoid cells

Abstract: Vitamin D receptor (VDR) knockout (KO) mice had fewer Citrobacter rodentium in the feces than wild-type (WT) mice and the kinetics of clearance was faster in VDR KO than WT mice. VDR KO mice had more IL-22 producing innate lymphoid cells (ILC), and more anti-bacterial peptides than WT mice. The increased ILC in the VDR KO mice was a cell autonomous effect of VDR deficiency on ILC frequencies. BM transplantation from VDR KO mice into WT resulted in higher ILC and colonization resistance of the WT mice. Disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 35 publications
1
61
0
1
Order By: Relevance
“…The authors noted that the dysbiosis observed in the knockout animals was accompanied by lower levels of tolerogenic dendritic cells in the gut and an increased sensitivity to intestinal inflammation [33]. More recent work by the group showed that the intestines of VDR-null mice were richer in IL-22-producing innate lymphoid cells (ILCs) and were resistant to the murine pathogen Citrobacter rodentium [34]. IL-22 is an innate immune cytokine produced by a subclass of ILCs (ILC3s) that signals through epithelial cells to bolster intestinal innate immunity through enhancing the production of AMPs and components of the mucosal layer [35,36].…”
Section: Discussionmentioning
confidence: 96%
“…The authors noted that the dysbiosis observed in the knockout animals was accompanied by lower levels of tolerogenic dendritic cells in the gut and an increased sensitivity to intestinal inflammation [33]. More recent work by the group showed that the intestines of VDR-null mice were richer in IL-22-producing innate lymphoid cells (ILCs) and were resistant to the murine pathogen Citrobacter rodentium [34]. IL-22 is an innate immune cytokine produced by a subclass of ILCs (ILC3s) that signals through epithelial cells to bolster intestinal innate immunity through enhancing the production of AMPs and components of the mucosal layer [35,36].…”
Section: Discussionmentioning
confidence: 96%
“…Deficiency of vitamin D and VDR signaling results in dysbiosis and impaired host defense against bacterial pathogens (26)(27)(28)(29)(30). Gut microbiota plays a role in the pathogenesis of cancer treatmenteinduced gastrointestinal mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in pregnant mice showed that maternal supplementation of 25 µg/kg vitamin D prior to an injection of 100 µg/kg of LPS-activated VDR signaling, which inhibited the pro-inflammatory NF-kB p65 pathway and genetic expression of the inflammatory cytokines TNF-α, IL-Iβ, and IL-6 (98). On the other hand, VDRs may contribute to maintenance of intestinal barrier function by preventing increased intestinal permeability, dysbiosis, inflammation, and a lack of immune tolerance in the gut (82).…”
Section: Discussionmentioning
confidence: 99%